Synthesis and characterization of CaBi4Ti4O15 thin films annealed by microwave and conventional furnaces - Simoes, A. Z.; Riccardi, C. S.; Ramirez, M. A.; Cavalcante, L. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
CaBi4Ti4O15 thin films were deposited by the polymeric precursor method and crystallized in a domestic microwave oven and conventional furnace. The films obtained for microwave energy are well-adhered, homogeneous and with good specularity, when treated at 700 degrees C for 10 min. The microstructure and the structure of the films can be tuned by adjusting the crystallization conditions. When microwave oven is employed, the films presented bigger grains with mean grain size around 80 nm. For comparison, films were also prepared by the conventional furnace at 700 degrees C for 2 h. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: bismuth layer; crystallization; microwave oven; ferroelectric properties